The mitogenome data of Holothuria (Mertensiothuria) leucospilota (Brandt,1835) from Malaysia - Nur Sabrina, Badrulhisham; Siti Najihah, Solehin; Han, Ming Gan *; Puteri Nur Syahzanani, Jahari; Faezah, Mohd Salleh; Aisyah, Mohamed Rehan; Kamarul, Rahim Kamarudin (Elsevier, 2023)
White threads fish Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) or locally known as bat puntil is a neritic marine organism, and it is widely distributed in Indo Pacific. They serve many important roles in ecosystem services and were discovered to contain many bioactive compounds that are useful for medicinal value. However, despite its abundance in Malaysian seawater, there is still a lack of records on H. leucospilota mitochondrial genome (mitogenome) from Malaysia. The mitogenome of H. leucospilota originating from Sedili Kechil, Kota Tinggi, Johor, Malaysia, is presented here. Whole genome sequencing was successfully sequenced using Illumina NovaSEQ6000 sequencing system and the mitochondrial-derived contigs were assembled using de novo approach. The size of the mitogenome is 15,982 bp which consists of 13 protein-coding genes (PCGs), 21 transfer RNAs, and 2 ribosomal RNAs. The overall composition of nucleotide bases was estimated to be 25.8% for T, 25.9% for C, 31.8% for A and 16.5% for G (with A + T content of 57.6%). Maximum likelihood phylogenetic tree analysis revealed that the mitochondrial Protein-Coding Genes (PCGs) sequence data from our H. leucospilota is closely related to H. leucospilota from accession number MK940237 and H. leucospilota from accession number MN594790, followed by H. leucospilota from accession number MN276190, forming sister group with H. hilla (MN163001), known as Tiger tail sea cucumber. The mitogenome of H. leucospilota will be valuable for genetic research, mitogenome reference and future conservation management of sea cucumber in Malaysia. The mitogenome data of H. leucospilota from Sedili Kechil, Kota Tinggi, Johor, Malaysia is available in the GenBank database repository with accession number ON584426.